Endothelial Dysfunction in Diabetes Mellitus: Possible Involvement of Endoplasmic Reticulum Stress? - Basha, Basma (Hindawi Publishing Corporation, 2012)
The vascular complications of diabetes mellitus impose a huge burden on the management of this disease. The higher incidence of cardiovascular complications and the unfavorable prognosis among diabetic individuals who develop such complications have been correlated to the hyperglycemia-induced oxidative stress and associated endothelial dysfunction. Although antioxidants may be considered as effective therapeutic agents to relieve oxidative stress and protect the endothelium, recent clinical trials involving these agents have shown limited therapeutic efficacy in this regard. In the recent past experimental evidence suggest that endoplasmic reticulum (ER) stress in the endothelial cells might be an important contributor to diabetes-related vascular complications. The current paper contemplates the possibility of the involvement of ER stress in endothelial dysfunction and diabetes-associated vascular complications.